Love beyond gluten: self-esteem, illness identity, and social support in romantic rejection concerns among adolescents with celiac disease - Shani, Maor; van Zalk, Maarten H. W. (Frontiers in Psychology, 2024)
Do adolescents and young people with celiac disease worry about the impact of their illness on their ability to find romantic partners? Fear of stigmatization, high perceived partner burden, or refraining from self-disclosure and compassion may manifest in romantic rejection concerns among adolescents and young adults with CD, contributing to lower health-related quality of life. In a sample of 165 German adolescents and young adults with CD, we found moderate levels of romantic rejection concerns, with no significant gender differences. Participants involved in romantic relationships expressed lower concerns of rejection, but similar preference for a “gluten-free partner”. In regression analysis, significant interactions revealed that higher acceptance of one’s illness in one’s identity predicted lower rejection concerns only among those with high self-esteem, while higher peer support mitigates rejection fears only among those with low self-esteem. Finally, romantic rejection concerns significantly predicted CD-specific health-related quality of life over and above other known predictors. The study underscores the crucial role of acceptance and support for managing romantic anxieties and the role of self-esteem in moderating these effects. The findings suggest specific pathways to reduce anxieties related to romantic rejection through counseling and interventions and emphasize the need to address psychosocial health concerns and anxieties within the context of a holistic treatment approach.